Tumor-associated neutrophils in renal cell carcinoma - Kovaleva, Olga V.; Sinyov, Vasiliy V.; Rashidova, Madina A.; Malashenko, Olga S.; Gratchev, Alexei (Frontiers in Immunology, 2026)
Renal cell carcinoma (RCC) is an immunogenic tumor in which tumor-associated neutrophils (TANs) and neutrophil extracellular traps (NETs) represent a functionally important component of the tumor microenvironment. Recent studies have revealed pronounced phenotypic heterogeneity of RCC-infiltrating neutrophils, including interferon-responsive, immunosuppressive PMN-MDSC-like, pro-angiogenic, and NET-forming subsets that cannot be adequately described by the classical N1/N2 model. Their polarization is shaped by ELR+ CXC chemokines (CXCL1, CXCL8), cytokine signals, systemic inflammation, hypoxia driven by VHL/HIF pathways, and tumor-intrinsic oncogenic alterations such as PTEN loss, ERβ- and c-Myc–dependent programs, as well as epigenetic remodeling. TANs exert predominantly pro-tumor functions in RCC, promoting T-cell exclusion and exhaustion, supporting angiogenesis and stromal remodeling, and facilitating epithelial–mesenchymal transition, venous invasion and metastasis. NETs, enriched in hypoxic and necrotic tumor regions and in venous tumor thrombi, further contribute to vascular occlusion, metastatic dissemination and local immune dysfunction, and are reflected by distinct transcriptional signatures. Clinically, high TAN density, activation markers and neutrophil/NET-associated gene signatures are consistently associated with aggressive tumor behavior, early recurrence, poor survival and resistance to VEGF-TKIs and immune checkpoint inhibitors. Emerging data also link neutrophil-rich stromal inflammation with the tumor resident microbiome, suggesting composite TAN-microbiome biomarkers for refined risk stratification. In this review, we summarize current knowledge on phenotypic diversity, regulatory circuits and functional programs of TANs and NETs in RCC, and discuss their prognostic and predictive significance, as well as therapeutic strategies aimed at chemokine blockade, complement modulation, NET inhibition and neutrophil re-education.